The Relationship Between Low Birth Weight and Premature Babies and Asphyxia Incidents at General Ahmad Yani Regional Hospital Metro City - Yus Rosella; Firda Fibrila; Sri Lestariningsih; Gangsar Indah Lestari (Jurnal Maternitas Kebidanan, 2026)
Asphyxia is a condition in which a baby cannot immediately breathe spontaneously and regularly. Babies with a history of fetal distress before birth will generally experience asphyxia at birth. The causes of asphyxia can originate from maternal, fetal, and placental factors. The presence of hypoxia and tissue ischemia cause functional and biochemical changes in the fetus. The impacts that can be caused by asphyxia include organ damage, severe hypoxia such as heart, lungs, liver, intestines, kidneys, and brain damage. This study generally aims to analyze the relationship between low birth weight and premature babies with the incidence of asphyxia at General Ahmad Yani Regional Hospital, Metro City. This study is a quantitative study with a case-control study design. The case population is all newborns with asphyxia, the control population is all newborns without asphyxia, the study sample amounted to 66 respondents consisting of 33 case samples and 33 control samples, which were taken using a simple random sampling technique. Analysis used the chi-square test with a 95% confidence level. The results of the study on asphyxia babies (case group) obtained a frequency distribution of low birth weight babies of 57.6% and a frequency distribution of premature babies of 68.2%. The results of the statistical test showed a relationship between low birth weight babies and the incidence of asphyxia with a p-value = 0.001 and OR = 0.154 that low birth weight babies have a 0.154 times greater risk of experiencing asphyxia, as well as premature babies with the incidence of asphyxia with a p-value = 0.034 and OR = 0.267 which means that premature babies will have a 0.267 greater risk of experiencing asphyxia than babies who are not premature. The conclusion of the study is a relationship between low birth weight and premature babies with the incidence of asphyxia. Efforts made to prevent the incidence of asphyxia can be a comprehensive pregnancy check-up, especially for mothers with high-risk factors such as too young/too old age, pregnancy with comorbidities, low nutritional status, or a history of problematic pregnancies and increasing promotive and preventive measures related to the risk of low birth weight and prematurity with the incidence of asphyxia.